Robust evaluations for duals of non-negative linear programs with box-constrained uncertainties - Ioslovich, Ilya; Gutman, Per-Olof (Algorithmic Operations Research, 2008)
Non-negative linear programs with box-constrained uncertainties for all input data and box-constrained variables are considered. The knowledge of upper bounds for dual variables is a useful information e.g. for presolving analysis aimed at the determination of redundant primal variables. The upper bounds of the duals are found by solving a set of special continuous knapsack problems, one for each row constraint.